2016
DOI: 10.1242/jeb.138370
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and microbial adjustments to diet quality permit facultative herbivory in an omnivorous lizard

Abstract: While herbivory is a common feeding strategy in a number of vertebrate classes, less than 4% of squamate reptiles feed primarily on plant material. It has been hypothesized that physiological or microbial limitations may constrain the evolution of herbivory in lizards. Herbivorous lizards exhibit adaptations in digestive morphology and function that allow them to better assimilate plant material. However, it is unknown whether these traits are fixed or perhaps phenotypically flexible as a result of diet. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 64 publications
(73 reference statements)
3
44
0
Order By: Relevance
“…A controlled feeding trial using L. ruibali demonstrated that the abundance of Desulfovibrio in the small intestine was correlated with whole‐animal fibre digestibility (Kohl et al . ). Further, the presence of Desulfovibrio may be important for reducing the H 2 by‐products associated with anaerobic fermentation in herbivorous iguanas (Hong et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A controlled feeding trial using L. ruibali demonstrated that the abundance of Desulfovibrio in the small intestine was correlated with whole‐animal fibre digestibility (Kohl et al . ). Further, the presence of Desulfovibrio may be important for reducing the H 2 by‐products associated with anaerobic fermentation in herbivorous iguanas (Hong et al .…”
Section: Discussionmentioning
confidence: 97%
“…Further details for housing and feeding of L. parvus and L. ruibali can be found in Kohl et al . (). We fed Phymaturus williamsi in the same manner as described in Kohl et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, ruminants fed fresh forage exhibit higher abundances of Oscillospira compared to those fed low‐fibre grain, and microscopy reveals that these bacteria associate with the surfaces of plant material in the gut (Mackie et al., ). Further, high‐fibre diets increase the abundance of Oscillospira in the guts of lizards (Kohl et al., ). The rodents in our study may maintain higher abundance of Ruminococcus and Oscillospira in the hindgut to aid in the digestion of dietary fibre.…”
Section: Discussionmentioning
confidence: 99%